Presynaptic congenital myasthenic syndrome with altered synaptic vesicle homeostasis linked to compound heterozygous sequence variants in RPH3A. Issue 3 (14th February 2018) - Maselli, Ricardo A.; Vázquez, Jessica; Schrumpf, Leah; Arredondo, Juan; Lara, Marian; Strober, Jonathan B.; Pytel, Peter; Wollmann, Robert L.; Ferns, Michael
Abstract: Background: Monogenic defects of synaptic vesicle (SV) homeostasis have been implicated in many neurologic diseases, including autism, epilepsy, and movement disorders. In addition, abnormal vesicle exocytosis has been associated with several endocrine dysfunctions. Methods: We report an 11 year old girl with learning disabilities, tremors, ataxia, transient hyperglycemia, and muscle fatigability responsive to albuterol sulfate. Failure of neuromuscular transmission was confirmed by single fiber electromyography. Electron microscopy of motor nerve terminals revealed marked reduction in SV density, double‐membrane‐bound sacs containing SVs, abundant endosomes, and degenerative lamellar bodies. The patient underwent whole exome sequencing (WES) and relevant sequence variants were expressed and studied in a mammalian cell line. Results: Chromosomal microarray studies and next generation sequencing (NGS) of mitochondrial DNA were unrevealing; however, NGS of genomic DNA showed two rare sequence variants in the gene encoding rabphilin 3a (RPH3A) . The paternally inherited variant c.806 G>A (p.Arg269Gln) involves a substitution of a conserved residue in the linker region, while the maternally inherited variant c.1390 G>T (p.Val464Leu) involves a conserved amino acid substitution in the highly conserved C2A region. Expression studies revealed that p.Arg269Gln strongly impairs the binding of rabphilin 3a to 14‐3‐3, which is a proposed regulator of synaptic transmission and plasticity. In contrast, the binding of rabphilin 3a to 14‐3‐3 is only marginally impaired by p.Val464Leu; thus, the pathogenic role of p.Val464Leu remains unclear. Conclusion: In summary, we report a patient with a multisystem neurologic disorder and altered SV regulation attributed to defects in RPH3A, which grants further studies of this gene in human disorders of synaptic transmission. Abstract : We report a patient with a complex phenotype characterized by failure of neuromuscular transmission, tremors and learning disabilities whose motor nerve terminals showed signs of disruptive synaptic vesicle homeostasis. The condition is attributed to sequence variants in RPH3A that alter both exocytosis and downstream endocytosis and synaptic vesicle recycling. The condition shows a favorable response to treatment with albuterol sulfate and encourages further research on the role of rabphilin 3a in human disorders of synaptic transmission.